2010
DOI: 10.1111/j.1526-4637.2010.00976.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors and Patterns of Chronic Pain Three Months after Cardiac Surgery in Taiwan

Abstract: Patients reporting a pattern of increasing pain starting about 10 days after surgery and holding negative beliefs about opioid use are at risk of developing chronic pain and may require more careful monitoring and pain treatment. The possible benefits of interventions that minimize pain during the weeks after surgery and that alter negative beliefs about opioid use should be examined in future research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…As reported in previous studies, 9,17,19,21,25,35 we found no significant association between the type of surgery (CABG or valve replacement, or both) and persistent postoperative pain. However, we found that the longer the surgery lasted, the less likely patients were to report any persistent postoperative pain.…”
Section: Discussionsupporting
confidence: 68%
See 4 more Smart Citations
“…As reported in previous studies, 9,17,19,21,25,35 we found no significant association between the type of surgery (CABG or valve replacement, or both) and persistent postoperative pain. However, we found that the longer the surgery lasted, the less likely patients were to report any persistent postoperative pain.…”
Section: Discussionsupporting
confidence: 68%
“…Results at earlier follow-up points are consistent with those reported in several prospective studies of shorter duration among cardiac surgery patients. 9,13,14,20,21,25 These prevalence rates are not negligible given that more than 400 000 patients undergo CABG annually in the United States 4 and that persistent postoperative pain affects patients' health-related quality of life. [7][8][9]19 The risk of persistent postoperative pain should be discussed with patients during preoperative counselling and perhaps included in informed consent for surgery.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations